Phosphatidylglycerol study as fetal lung maturation parameter after dexamethasone administration for women at risk of preterm birth - Rahmadani, Rizal Umar; Sulistyono, Agus; Yulistiani, Yulistiani; Yahya, Muhammad (Folia Medica Indonesiana, 2017)
Phosphatidylglycerol is an important indicator of fetal lung maturation, which plays a role in stabilizing surfactant lipoprotein complex. Corticosteroid antenatal can stimulate the synthesis of pulmonary surfactant in infants with preterm birth. The objective of this study is to examine the phosphatidylglycerol levels as fetal lung maturation parameter after dexamethasone administration in women with preterm birth compared to L/S ratio parameter. This study was prospective longitudinal (cohort). The samples were pregnant women with preterm birth risk at 28-34 weeks gestation getting the therapy of antenatal dexamethasone 6 mg IM every 12 hours given 4 times in 48 hours. The samples were 17 patients. Determination of L/S ratio and PG levels was performed by ELISA. The study was conducted from May - November 2015 and reviewed to obtain ethics eligibility permit by the research ethic committees of Dr. Soetomo General Hospital. The results show that the mean value of L/S ratio is 2.28 with a range of 1.35 to 9.06 and the mean of PG level is 1.17 with a range from 0 to 3.79. L/S ratio and PG show no significant relationship between the two of them. Increased levels of PG on the gestational age of 28-32 weeks have not demonstrated clinically significant changes yet. The highest PG level occurs in the gestational age of 32-34 weeks.